2009
DOI: 10.4141/cjas09002
|View full text |Cite
|
Sign up to set email alerts
|

Potential of warm-season annual forages and Brassica crops for grazing: A Canadian Review

Abstract: . 2009. Potential of warm-season annual forages and Brassica crops for grazing: A Canadian Review. Can. J. Anim. Sci. 89: 431Á440. Extension of the grazing season beyond the normal perennial grazing season has been identified as a potential mechanism to reduce the cost of production on Canadian cow-calf operations. This review will provide an overview of the potential use of warm-season and Brassica crops including corn (Zea mays), Golden German foxtail millet (Setaria italica L. Beauv.), kale (Brassica olerac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Forage brassicas are sometimes equated to concentrate feeds due to their relatively low aNDF and high CP and digestibility. Although grazing forage brassicas can affect rumen function unless roughage (e.g., hay) is provided (McCartney et al, 2009), mixtures with warm‐season (e.g., sorghum [ Sorghum bicolor (L.) Moench], sudangrass [ Sorghum bicolor (L.) Moench], or millets) and cool‐season grasses (e.g., small grains) have also been evaluated as a means of increasing DM and fiber content provided to beef cattle (Sedivec et al, 2011). Even though our study did not include grazing evaluations, previous evidence suggests that strip grazing should be used as a means to avoid trampling of the stand and to decrease waste, especially when soils are wet (Sedivec et al, 2011).…”
Section: Implications For Producersmentioning
confidence: 99%
“…Forage brassicas are sometimes equated to concentrate feeds due to their relatively low aNDF and high CP and digestibility. Although grazing forage brassicas can affect rumen function unless roughage (e.g., hay) is provided (McCartney et al, 2009), mixtures with warm‐season (e.g., sorghum [ Sorghum bicolor (L.) Moench], sudangrass [ Sorghum bicolor (L.) Moench], or millets) and cool‐season grasses (e.g., small grains) have also been evaluated as a means of increasing DM and fiber content provided to beef cattle (Sedivec et al, 2011). Even though our study did not include grazing evaluations, previous evidence suggests that strip grazing should be used as a means to avoid trampling of the stand and to decrease waste, especially when soils are wet (Sedivec et al, 2011).…”
Section: Implications For Producersmentioning
confidence: 99%
“…Certain negative effects on animal health associated with grazing legume green manures, cereals, or brassicas have been observed (Gardner and Faulkner 1991;Johnson et al 1992;Panciera et al 1992;Hannaway and Larson 2004;Rao et al 2005;McCartney et al 2008McCartney et al , 2009McCartney and Fraser 2010); however, animal health risks posed by grazing can generally be minimized through crop cultivar selection and grazing management.…”
Section: Grazing In Annual Cropping Systemsmentioning
confidence: 99%
“…Grazing green manures and annual forages, rather than soilincorporating them or harvesting them as green feed or silage, may offer some economic benefits as well as the ecological benefits of integrating livestock directly into annual cropping systems (Thiessen Martens and Entz 2011), though only limited research has been conducted in this region (McCartney et al 2009;McCartney and Fraser 2010).…”
Section: Cover Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concern with this early seeding date is weed control. Millets do not compete well with weeds until they are 6 to 8 inches tall (Alberta Agriculture 2004;Reimer and Gaudiel 1984, 1986: McCartney, Fraser, and Ohama 2009. May et al (2007) found that seeding Golden German millet earlier than 10 June may be advantageous in the long term if weed control can be maintained.…”
Section: Discussionmentioning
confidence: 96%